2020
DOI: 10.3171/2020.6.focus20315
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the L5 nerve root during anterior lumbar interbody fusion at L5–S1: case series and review of the literature

Abstract: OBJECTIVENerve root injuries associated with anterior lumbar interbody fusion (ALIF) are uncommonly reported in the literature. This case series and review aims to describe the etiology of L5 nerve root injury following ALIF at L5–S1.METHODSThe authors performed a single-center retrospective review of prospectively collected data of patients who underwent surgery between 2017 and 2019 who had postoperative L5 nerve root injuries after stand-alone L5–S1 ALIF. They also reviewed the literature with regard to ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…The article notes an outcome of postoperative neuropraxia in their patient series due to potential direct iatrogenic injury to the nerve roots during discectomy or disk preparation. 22 Such are injuries which may be detected by IONM. The described patient example provides evidence of the benefit of IONM to avoid irreversible iatrogenic nerve root injury.…”
Section: Discussionmentioning
confidence: 99%
“…The article notes an outcome of postoperative neuropraxia in their patient series due to potential direct iatrogenic injury to the nerve roots during discectomy or disk preparation. 22 Such are injuries which may be detected by IONM. The described patient example provides evidence of the benefit of IONM to avoid irreversible iatrogenic nerve root injury.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes were suggested for motor weakness in one study. Dowlati et al [ 14 ] suggested that an excessive increase in the height of the disc space causes stretching of the nerve roots, resulting in neuropraxia. In their study of patients with nerve root injury, the anterior and posterior disc heights increased by 134% and 92%, respectively, while the foraminal height increased by 50%.…”
Section: Discussionmentioning
confidence: 99%
“…A review article on iatrogenic neurologic deficits after lumbar spine surgery reported a 4.1% rate of newonset neurologic injury after anterior or lateral lumbar fusion surgery [10]. Postoperative L5 radiculopathies after L5-S1 ALIF procedures have been described [14,15]. The postoperative deficit has most commonly been attributed to a stretch neuropraxia from over distraction of the disk L5-S1 space.…”
Section: Discussionmentioning
confidence: 99%
“…Oversizing the graft and aggressive malleting with the cage trial should be avoided. These maneuvers have been associated with L5 radiculopathy after L5-S1 ALIF [14,15]. The surgeon should also account for the geometric shape of the interbody cage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation